2016
DOI: 10.1159/000450750
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Determinants of Adherence to Oral Anticoagulants in Stroke Patients with Atrial Fibrillation in Clinical Practice

Abstract: Background: Vitamin K antagonists (VKAs) and non-VKA oral anticoagulants (NOACs) are beneficial in patients with stroke and atrial fibrillation (AF). However, little is known about frequency and determinants of adherence to NOACs/VKAs in clinical practice. Methods: This is a single-center explorative study from the Novel Oral Anticoagulants in Stroke Patients (NOACISP)-LONGTERM registry. We included consecutive AF-stroke patients treated with NOACs/VKAs and followed up for 3-24 months. Adherence was assessed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 28 publications
3
39
0
7
Order By: Relevance
“…There are only a few studies on stroke patients presenting self-report adherence rates. These studies reported varying rates for high adherence (between 50% and 84%) (31,32,33). Our findings should be interpreted carefully because the assessment of adherence with a patient self-report approach may cause bias.…”
Section: Discussionmentioning
confidence: 66%
“…There are only a few studies on stroke patients presenting self-report adherence rates. These studies reported varying rates for high adherence (between 50% and 84%) (31,32,33). Our findings should be interpreted carefully because the assessment of adherence with a patient self-report approach may cause bias.…”
Section: Discussionmentioning
confidence: 66%
“…It may, however, be important to distinguish between degrees of cognitive impairment, as individuals with more severe impairments and dementia may rely on caregivers to administer medications, leading to increased adherence [ 17 , 47 ], while those with mild cognitive impairment managing their own medications may be most at risk of sub-optimal adherence. The association between cognitive impairment and adherence, if it exists, may in fact be U-shaped, with poorer adherence in patients with milder cognitive impairments who self-administer their medications, and better adherence in patients with more severe impairments who receive support with medication taking.…”
Section: Discussionmentioning
confidence: 99%
“…This should encourage us to look for better strategies to improve secondary stroke prevention, such as ensuring patients' adherence to treatment. The NOACISP-LONGTERM registry showed 78.4% of the patients to be fully adherent with a median follow-up of 12 months, and a recent systematic review showed that up to 30% of the patients with AF are non-adherent to any OAC (22,41). Likewise, a Spanish study suggested that only 41.4% of the patients are treated following the current Spanish recommendations in clinical practice (42).…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that stroke patients are at high risk both of ischemic and hemorrhagic strokes, and prevention of both are the main objectives in this specific population, it seems necessary to monitor the effects of OAC in non-selected patients in clinical practice. Several registries have been published in recent years to study the use of the various oral anticoagulant treatments in stroke patients (18)(19)(20)(21)(22)(23)(24)(25)(26), mainly evaluating clinical outcomes such as stroke recurrence, cerebral hemorrhage, or functional outcome. Other published registries were focused on the use of radiological markers such as cerebral microbleeds or white matter hyperintensities in order to stratify the hemorrhagic risk in this specific population (27,28).…”
Section: Introductionmentioning
confidence: 99%